PENGETAHUAN TANPA SUBYEK PENAHU: Kajian Kritis atas Epistemologi Popper - Valentinus . (Studia Philosophica et Theologica, 2011)
Subject and object relations is problematic. This problem is registered in the history of knowledge, especially in epistemology. The problem rises from the ontological status of subject and object. Man, as a subject, is homo rationale. Ratio means non-physic; meanwhile, object belongs to the universe of material being. If knowledge means an object’s mode of being in subject, the question is thus what kind of relation do subject and object have? What is the status of the object in this problematical relation? Karl Raimund Popper has elaborated this question, and this article wants to present this elaboration.